2022
DOI: 10.1371/journal.pone.0273206
|View full text |Cite
|
Sign up to set email alerts
|

Maternal stress induced anxiety-like behavior exacerbated by electromagnetic fields radiation in female rats offspring

Abstract: There is a disagreement on whether extremely low frequency electromagnetic fields (ELF-EMF) have a beneficial or harmful effect on anxiety-like behavior. Prenatal stress induces frequent disturbances in offspring physiology such as anxiety-like behavior extending to adulthood. This study was designed to evaluate the effects of prenatal stress and ELF-EMF exposure before and during pregnancy on anxiety-like behavior and some anxiety-related pathways in the hippocampus of female rat offspring. A total of 24 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…In the present study, we examined the effects of PS, ELF‐EMF, and simultaneously PS and ELF‐EMF on anxiety‐like behaviors, and expression of synaptic plasticity associated proteins (BDNF and GAP‐43) and neural cell apoptotic factor, cas‐3. As it was depicted previously (Hosseini et al., 2022 ), we observed that ELF‐EMF and stress groups showed anxiety‐like behavior. We found that female offspring which their mothers underwent PS and ELF‐EMF together, showed severe anxiety‐like behaviors, which were more intensive than those whose mother experienced only PS (group stress) or only ELF‐EMF (group ELF‐EMF).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, we examined the effects of PS, ELF‐EMF, and simultaneously PS and ELF‐EMF on anxiety‐like behaviors, and expression of synaptic plasticity associated proteins (BDNF and GAP‐43) and neural cell apoptotic factor, cas‐3. As it was depicted previously (Hosseini et al., 2022 ), we observed that ELF‐EMF and stress groups showed anxiety‐like behavior. We found that female offspring which their mothers underwent PS and ELF‐EMF together, showed severe anxiety‐like behaviors, which were more intensive than those whose mother experienced only PS (group stress) or only ELF‐EMF (group ELF‐EMF).…”
Section: Discussionsupporting
confidence: 88%
“…Each week the stress procedure consists of eight different stress modes (Table 1 ) (Hosseini et al., 2022 ): two periods of stroboscopic lighting (300 flash/min), one period of dry cage, two periods of noise (80 db), two periods of 45° cage tilt, one period of pair housing, and periods of water and food deprivation in which water deprivation was empty water bottles and food deprivation was followed by limited food intake (Hosseini et al., 2022 ; Salehpour et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are expressed as means ± SEM, *p < 0.05, unpaired t-test. It has been reported that the EMR activates the HPA axis (Gupta et al, 2019) and its receptors (Hosseini et al, 2022), influencing neurotransmitter release by activating voltage-gated calcium channels and elevating intracellular calcium levels (Pall, 2016;Othman et al, 2017) in mice. In this study, we observed a significant increase in serum CORT and CRH levels in mice following long-term exposure to dual-frequency EMR, suggesting an association between anxietylike behavior and activated HPA axis.…”
Section: 6mentioning
confidence: 99%